CROSS-CULTURAL WEB DESIGN STUDY: RESEARCHERS’CHALLENGING TASKS IN DEVELOPING COUNTRIES - Goh, Chu Hiang (Asia Pacific Institute of Advanced Research (APIAR), 2016)
Cross-cultural web design research in developing countries especially in Southeast Asia is challenging due to its cross-cultural constraints and complexities. Drawn from analysis and extensive literature review in cross-cultural studies, HCI and design theories, the paper presents the current research trends and challenges faced by contemporary researchers in this area. Myriad of definitions and understanding of culture; uncritical adoption of models and culture theories; issues of etic, emic and the problems of pseudo-etic claims in research findings; and the significant role of designer as primary decision-maker in design processes, are the challenges delineated in this paper. It is crucial to examine these issues to secure the best practice in cross-cultural web design study. The paper concludes by indicating a substantial misdirection in the current research trends and suggests that a redirection of research approach is essential to improve the web service in government websites in order to further enhance social and economic development. Five significant guidelines to conduct cross-cultural web design research in developing countries are thus proposed.